INNOVATIVE AGRICULTURE: ADVANCING COTTON CULTIVATION IN MARATHWADA REGION WITH IOT. - Shaikh, Farooque Yasin; Bansod, Dr. Nagsen S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper explores the application of IoT (Internet of Things) technologies to enhance cotton crop yield in the Marathwada region of India. Cotton cultivation in Marathwada faces significant challenges such as water scarcity, pest infestations, and unpredictable weather conditions, which impact crop productivity and farmer livelihoods. The objectives of this study are to investigate how IoT can address these challenges and to assess its effectiveness in improving crop yield. The methodology involves deploying various IoT devices including soil moisture sensors, weather stations, and pest monitoring systems across cotton fields in the region. Data collected from these devices are analyzed to understand soil conditions, optimize irrigation schedules, predict weather patterns, and implement timely pest management strategies. The study compares the performance of IoT-enabled fields with traditional farming methods to evaluate the impact on crop yield, water usage efficiency, and overall farm sustainability. Key findings indicate that IoT-based precision agriculture techniques significantly enhance crop yield by providing real-time data insights for informed decision-making. The adoption of IoT reduces water consumption through optimized irrigation practices and improves pest control measures, thereby minimizing crop losses. Furthermore, IoT facilitates remote monitoring and management, enabling farmers to respond promptly to changing agricultural conditions. The implications of this research highlight the potential of IoT to revolutionize agriculture in Marathwada by offering sustainable solutions that increase productivity and resilience to climate variability.